The evaluation of parents’ knowledge about psychophysical development of the 0-12 months old children - Weber-Nowakowska, Katarzyna; Drewniak, Katarzyna; Kulik, Anita; Chilman, Agata; Gębska, Magdalena (Journal of Education, Health and Sport, 2023)
Introduction: A process of psychomotor development should take place harmoniously according to a fixed plan. Because of the fact, that not every child develops properly, parents ought to possess basic knowledge of child’s psychomotor development. It could enable them to notice any possible abnormalities and turn to a specialist for help in time. Aim: The aim of the study is to assess parents’ knowledge about the psychomotor development of children aged 0-12 months and the impact of selected socio-demographic factors on the level of this knowledge Materials and methods: The research involved 111 parents who filled in the questionnaire form on psychomotor development of a child in its first year. Results: It has been proven that a general level of parents’ knowledge ranges from low to good. Moreover, based on the research it can be claimed, that people who graduated from universities gain better knowledge on a person’s development than people who didn’t. Similarly, parents with a bigger amount of children and what’s connected, better experience, achieve better results. Finally, a large majority of parents claim that their knowledge is better that it really is. Conclusions: Comparing the outcome with the results of other researchers it can be concluded, that the level of knowledge on child’s psychomotor development is rather low. The reason of that might be the lack of needed education on the area. Taking into consideration a quite wide range of available sources of information, parents can find many possibilities to broaden their knowledge. To improve the situation various actions encouraging self-improvement of parents’ level of knowledge should be introduced. In the future a similar research should take place to check if the level of awareness of this issue is heightened.